PREFACE TO SPECIAL THEME, PART 1: Toward a better understanding of Lake Simcoe through integrative and collaborative monitoring and research - Michelle Elaine Palmer; Véronique P Hiriart-Baer; Rebecca L North; Michael D Rennie (Freshwater Biological Association, 2013)
This special section of Inland Waters features the first of numerous papers that highlight trends and insights emerging from decades of ecological monitoring and research activities on Lake Simcoe, Canada. Lake Simcoe is the largest lake in southern Ontario after the Laurentian Great Lakes. Like most large lakes, Simcoe has been negatively impacted over the past century by human activities, which accelerated dramatically around the 1930s (Hawryshyn et al. 2012). Phosphorus (P) loading from point and nonpoint sources caused excessive growth of plants and algae that consume hypolimnetic oxygen during decomposition, which limited coldwater fish habitat and contributed to the recruitment failure of popular sportfish such as lake trout (Salvelinus namaycush) and lake whitefish (Coregonus clupeaformis; Evans et al. 1996). The establishment in recent decades of invasive fish, invertebrates, and plants is changing lake habitat, food webs, and native species dynamics (Evans et al. 2011, Ginn 2011, Ozersky et al. 2011). Increasing air temperature associated with climate change has prolonged thermal stratification and shortened the period of ice cover (OMOE et al. 2009, Stainsby et al. 2011). Metals and organic pollutants originating from urban and industrial sources have accumulated in lake and tributary sediments (Helm et al. 2011, Landre et al. 2011), potentially affecting aquatic biota and increasing the risk associated with human fish consumption (Gewurtz et al. 2011, Lembcke et al. 2011). Additionally, the cumulative effects of these and other stressors have drastically altered aquatic communities (Depew et al. 2011, Ginn 2011, Jimenez et al. 2011, Winter et al. 2011).In response to public concern about the ecological health of the lake, the Lake Simcoe Protection Act was approved by the Government of Ontario in 2008 with a mandate to protect and restore the Lake Simcoe watershed (Government of Ontario 2008). The Act established the Lake Simcoe Protection Plan (LSPP; OMOE et al. 2009) that identifies a number of targets and indicators to characterize environmental health in the Lake Simcoe watershed and details 119 policies and actions to achieve these targets. Scientific monitoring and research play an integral role in the success of the LSPP, which supports an ecosystem approach to informing policies and actions, taking into account the interconnectedness of the lake and watershed. The LSPP mandates the enhancement of current monitoring programs, development of new monitoring programs, and the promotion and implementation of research projects that build upon existing science to continually update management decisions as part of an adaptive management approach.The challenges posed by the LSPP necessitate collaborative research efforts and sharing of responsibilities, resources, and knowledge among federal, provincial, and local governments, academics, conservation authorities, agricultural, commercial, and industrial sectors, First Nations communities, the general public, and other stakeholders. The collection of papers shows the value of a collaborative approach and demonstrates how strong partnerships can facilitate integrative approaches to scientific monitoring and research efforts being used to protect Lake Simcoe.